The Image of the Anti- Hero in James Joyce's Ulysses (Journal of the College of Languages (JCL), 2006)
The hero traditionally has such admirable traits as courage, fortitude,chivalry and patriotism. In the literary works, the hero is the leadingcharacter and the pivot around which all the characters and the eventsrevolve. The characteristics of the hero usually reflect the cultural valuesof his time. Because, in each age, Man's attitudes towards himself and theworld change, different images of the hero emerge.In Greek Mythology, the hero is frequently favoured by the gods;therefore, he is himself semi-divine. The Greek hero is of princely birthand is endowed with good physique, exceptional strength, skill inathletics and battle, energy and eloquence, like Odysseus who is the heroof the Odyssey, long epic poem traditionally ascribed to the Greek poetHomer. Odysseus is the king of Ithaca and he is a valorous, mighty leaderwho took part in the siege of Troy. On his way back to Ithaca, after theend of the war, he passed through many dangerous adventures in whichhe encountered ruthless monsters such as Cyclopes, a giant with one eye,and Scylla, an equally dreadful monster with six head. 1